The interest of uterine artery ligation in gynecological surgery: the experience of Obstetrics and Gynecology Department at Mohammed VI University Hospital in Oujda, Morocco - Meziyane, Jihane; El Ghali, El Hassan; Graiti, Ghizlane; Taheri, Hafsa; Saadi, Hanane; Mimouni, Ahmed (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Ligation of the uterine arteries is the placement of a clip or a ligature on the uterine artery allowing the devascularization of the irrigated area of the uterus. Indeed, in order to limit uterine bleeding during a myomectomy or a difficult hysterectomy, primary ligation of the uterine arteries is proved helpful. Our work aimed to discuss the indications for artery ligation uterine, describe its different techniques and assess its effectiveness and benefit. Our work was a retrospective analytical descriptive and mono-centered study, involving 21 patients who underwent vascular ligation of the uterine artery, as first stage of surgery, regardless of the approach, as part of a myomectomy/polymyomectomy or hysterectomy, in the Gynecology And Obstetrics Department at the Mohammed VI University Hospital of Oujda, over a period of thirty-four months, going from January 2019 to October 2021. The average age of the patients in our study was 39 years old. 66.7% of patients benefited from a myomectomy/polymyomectomy while 28.5% underwent a hysterectomy. The first technic was laparoscopy in 52.3% of cases and the second laparotomy in 47.7% of cases. The ligation of the uterine arteries was performed bilaterally, permanently by vascular clips in all patients. Blood loss was estimated to be 121 ml on average with extremes of 45 and 350ml, the hemoglobin level decreased by an average of 0.7 g/dl and none of the patients in our study required an intraoperative or postoperative transfusion. Occlusion of the uterine arteries seems to have a remarkable effect in reducing blood loss during gynecological surgery and does not increase the risk of intra or postoperative complications. However, more studies are required to assess its impact on subsequent fertility.